Factor IX Deventer-Evidence for the Heterogeneity of Hemophilia BM - Bertina, R M; Linden, I K van der (Thrombosis and Haemostasis, 1982)
Factor IX Deventer was isolated from the plasma of a patient with severe hemophilia B. The patient was classified as BM because of an abnormal prolongation (2.1 times) of the ox-brain prothrombin time, that could be corrected by addition of antifactor IX serum. Experiments with the isolated factor IX Deventer showed that one of the two peptide bonds involved in the proteolytic activation of factor IX cannot be cleaved by physiological or non-physiological activators (XIa and RVV-X, respectively). Such a defect can explain why the molecule has no procoagulant activity. At present it is not clear why this defect makes factor IX Deventer such an effective inhibitor of the ox-brain prothrombin time. It is proposed that hemophilia BM is a heterogeneous disorder.
Keywords: Hemophilia BM; Factor IX BM; Factor IX Deventer; Activation of factor IX BM